Physical health behaviors of gardening and non-gardening parents and their children - Smith, Ann Marie (Kansas State University, 2010)
Professionals in health promotion are starting to look at gardening as a strategy for health behavior change. This popular leisure time activity provides access to physical activity and fresh fruits and vegetables for consumption, two behaviors consistently recommended for optimum physical health. Coupled with a lifestyle low in sedentary behavior these behaviors can offset the health risks of the prevailing trends of overweight and obesity. Spending time outdoors is associated with higher levels of physical activity, while screen based behaviors are associated with unhealthy eating. No studies to date have looked at the health behaviors of gardeners, or the effects it may have on their family’s health behaviors. The purpose of this report is to examine, through descriptive research, the health behaviors of gardening and non-gardening parents and their fourth or fifth grade child. Surveys were administered to a convenience sample of 366 fourth and fifth grade students and their guardians within a school district in Riley County, Kansas. The survey assessed the physical health behaviors mentioned above; comparisons were made according to parental classification of gardener (n=189) or non-gardener (n=177). Significant association was found with gardening classification and adult self-reports of the number of days and amount of time respondents participated in moderate to vigorous physical activity. The median days per week parents reported participation in moderate to vigorous physical activity was 3 for non-gardeners, and 4 for gardeners and was influenced by gender. Eighty-seven percent of gardeners compared to 59.3% of non-gardeners reported meeting the current physical activity recommendation of 150 minutes per week of moderate intensity activity.
Keywords: gardening; health behaviors; parents; physical activity; fruit and vegetable consumption; sedentary behavior; Health Sciences, Public Health (0573)